Contribution of Suspension Bogies’ Aerodynamic Loads to the Dynamic Characteristics of a High-temperature Superconducting Maglev Train Running under Crosswind - Z. P. Li; X. F. Wang; Y. M. Pan; Y. Ding; P. F. Liu; Z. G. Deng (Journal of Applied Fluid Mechanics)
The suspension bogies at the bottom of the high-temperature superconducting pinning (HTS) maglev trains are critical components, responsible for levitation, guidance, shock absorption, etc. This research delves into the aerodynamic load features of the suspension bogies on HTS maglev trains when operating under various crosswind conditions. By employing the unsteady Reynolds-averaged Navier-Stokes (URANS) equations coupled with the shear stress transport (SST) k-ω turbulence model, we elucidate the dynamic impact of these aerodynamic loads on the vehicle's overall performance, thereby offering valuable insights into the structural design of the train. The accuracy of the numerical method was confirmed by using wind tunnel test data from the scaled ICE-2 model. Furthermore, by adopting a strategy of partitioning the aerodynamic load, the impact on the overall vehicle dynamics performance is analyzed, and the operational safety of the train under different crosswind scenarios is assessed with Multi-body Dynamic (MBD) simulations. The research results indicate that the first bogie at the bottom of the head car contributes the most to the unsteady fluctuations of the aerodynamic load. Additionally, the partitioned loading method has a significant impact on the simulation results, which can better assess the safety of the train's operation under crosswinds. The research findings can provide references for the system design and engineering application of the HTS maglev train.